Current Status of the Mollicute (Mycoplasma) Lung Disease: Pathogenesis, Diagnostics, Treatment and Prevention - Giono-Cerezo, Silvia; Estrada-Gutiérrez, Guadalupe; Rivera-Tapia, José Antonio; Yáñez-Santos, Jorge Antonio; Díaz-García, Francisco Javier (IntechOpen, 2012)
None